Respuesta :

[tex]\bf (\stackrel{x_1}{4}~,~\stackrel{y_1}{5})\qquad (\stackrel{x_2}{-6}~,~\stackrel{y_2}{15}) ~\hfill \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{15}-\stackrel{y1}{5}}}{\underset{run} {\underset{x_2}{-6}-\underset{x_1}{4}}}\implies \cfrac{10}{-10}\implies -1 \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{5}=\stackrel{m}{-1}(x-\stackrel{x_1}{4}) \\\\\\ y-5=-x+4\implies y=-x+9[/tex]

this is correct good job!

Step-by-step explanation: